Simulation of Arc Discharge in an Argon/Methane Mixture, Taking into Account the Evaporation of Anode Material in Problems Related to the Synthesis of Functional Nanostructures - Almaz Saifutdinov; Boris Timerkaev (Nanomaterials)
In this work, within the framework of a self-consistent model of arc discharge, a simulation of plasma parameters in a mixture of argon and methane was carried out, taking into account the evaporation of the electrode material in the case of a refractory and non-refractory cathode. It is shown that in the case of a refractory tungsten cathode, almost the same methane conversion rate is observed, leading to similar values in the density of the main methane conversion products (C, C2, H) at different values of the discharge current density. However, with an increase in the current density, the evaporation rate of copper atoms from the anode increases, and a jump in the I–V characteristic is observed, caused by a change in the plasma-forming ion. This is due to the lower ionization energy of copper atoms compared to argon atoms. In this mode, an increase in metal–carbon nanoparticles is expected. It is shown that, in the case of a cathode made of non-refractory copper, the discharge characteristics and the component composition of the plasma depend on the field enhancement factor near the cathode surface. It is demonstrated that increasing the field enhancement factor leads to more efficient thermal field emission, lowering the cathode’s surface temperature and the gas temperature in the discharge gap. This leads to the fact that, in the arc discharge mode with a cathode made of non-refractory copper, the dominant types of particles from which the synthesis of a nanostructure can begin are, in descending order, copper atoms (Cu), carbon clusters (C2), and carbon atoms (C).